Condition of the gastrointestinal tract motor function in abdominal injury - Safronov, Danila (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2019)
Introduction. Injuries are a large medical and social problem. It takes many lives and is often a cause of disability. Objectives. The work is devoted to the study of the motor-evacuation function (MEF) of the gastrointestinal tract (GIT) in patients with closed abdominal injury of varying severity. Materials and methods. 125 patients with isolated or combined blunt abdominal trauma were under observation. The main criterion for the inclusion of patients in the study was the presence of injury to the abdomen and / or retroperitoneal space, confirmed while surgery or using instrumental methods of examination. The structure of injuries was dominated by a combined trauma, which was observed in 104 (83.2%) victims; in 21 (16.8%) patients abdominal injury was isolated or multiple. Evaluation of the MEF of the gastrointestinal tract was carried out using a technique developed with the participation of the author on the basis of the available indicators widely used in practice. The severity of the injury was determined on an ISS scale. Results. The results showed that the predominant part of patients with abdominal trauma (62.4%) had a violation of gastrointestinal MEF upon admission; in 21% of patients, the state of function at the border of functional compensation was noted, and only in 16% of persons, the MEF of the gastrointestinal tract was rated as moderately and completely compensated. By severity of injury, a group of patients with moderate severity (47.2%) prevailed; a mild injury was observed in 35.2% of patients, severe injury was diagnosed in 16%, and a super-severe one was in 1.6% of injured people. Conclusions. The possibility of using the MEF indicators of the gastrointestinal tract as one of diagnostic criteria for the severity of a blunt abdominal injury is assumed.